Promoting exercise prescription among community health centers physiotherapists - Wibowo, Tri (BKM Public Health and Community Medicine, 2021)
Background: Based on Riskesdas 2018, the number of Non-Communicable Diseases in Indonesia continues to increase nationally, Heart Disease-Stroke 10.9%, Cancer at 1.8%, Diabetes at 8.5%, Hypertension at 34% (Ministry of Health, 2018). Objective: Looking for a model of appropriate and efficient health services to prevent and control the number of Non-Communicable Diseases (NCDs) in primary care. Result: Prevention-based Physiotherapy services with prescription Physical activity/Sport is a modern preventive-based medical concept that is effective and efficient in preventing several non-infectious diseases.